Value, Identity and Place: unearthing the emotional geographies of the extractive sector. Issue 2 (3rd April 2017) - Ey, Melina; Sherval, Meg; Hodge, Paul
ABSTRACT: The practice of natural resource extraction remains a key function of the global economy, and has been the subject of a considerable body of research, across multiple academic disciplines. Growing awareness of the economic, socio-cultural and ecological aspects of extractive practices (and their impacts) have also forced change in the way in which this research is conceptualised. Yet, despite conceptual shifts, a lack of engagement with the felt and emotive dimensions of the extractive sector remains striking. As a complex and highly contested industry, acknowledging emotion is crucial to breaking down problematic representations of the sector as a 'rational', 'economic' and emotionless space. This paper emphasises the need to engage and prioritise emotional and affective registers when thinking about, and representing, the extractive sector. Specifically, this paper explores the role of emotion in problematising approaches to the material across the sector, as well as in unsettling the often taken-for-granted and highly gendered workplace identities that characterise the sector. Finally, this paper will highlight the importance of validating emotion in legitimising important relationships to place that conflict with extractive practices. In essence, this paper calls for more emotionally attuned approaches to the extractive sector, in order to engage with its profoundly emotive dimensions and impacts.